THE EFFECT OF CATHETER TRACTION DIRECTION ON HEMOSTASIS AND PAIN POST TURP - Ariani, Devintha Tiza; Umbas, Rainy; Rasyid, Nur; Suprabawati, Tri Endah (Indonesian Journal of Urology, 2012)
Objective: To compare the effect the direction of catheter traction to the abdomen with direction to the leg on hemostasis and pain degree post-TURP. Material & Method: 122 patients with BPH came to Cipto Mangunkusumo Hospital and Budi Asih Hospital, Jakarta during the period between January 2005 to January 2011. Results: 101 patients with retention and 21 patients without retention were included in this study. Resected tissue weight was 22,95 grams, irrigation time was 2,24 days, catheterisation time was 3,97 days, and post TURP hospitalization was 3,9 days. Hb decline was 1,17g/dl. There was no statistical difference on Hb decline between leg direction 1,23 g/dl and abdominal direction 1,12 g/dl. Resected tissue weight in abdominal direction group was 25 grams, while in leg direction group was 21 grams. Irrigation time in abdominal direction group was 2 days while in leg direction group was 2,4 days. Catheterisation time in abdominal direction group was 3,3 days while in leg direction was 3,4 days. Post TURP hospitalization in abdominal direction group was 3,7 days while in leg direction groups was 4,2 days. In this study resected tissue weight, irrigation time, catheterisation time, and hospitalization time. There were 64 patients with pain degree registration, patients with abdominal traction had mean pain degree scale 1,52 and 33 patients with leg traction had pain degree scale 2,97, in this study this differences were significant. Conclusion: Abdominal traction post TURP was statistically difference on shortened postoperative irrigation and catheterisation time, including reduced post TURP hospitalization and pain degree. Abdominal traction was recommended from this study to be used as the reference standard for changing leg traction. Keywords: Catheter traction, visual analog scale, hemostasis, transurethral resection of the prostate.